2021
DOI: 10.1177/23337214211004366
|View full text |Cite
|
Sign up to set email alerts
|

Returns to Educational and Occupational Attainment in Cognitive Performance for Middle-Aged South Korean Men and Women

Abstract: Background: Gender differences in late middle-age cognitive performance may be explained by differences in educational or occupational attainment rates, or gender-patterned returns of similar education and occupation to cognitive reserve. We tested these competing hypotheses in the historically highly gender unequal context of South Korea. Methods: Data came from the 2006 wave of the Korean Longitudinal Study of Aging. We included adults aged 45–65 years. Using quantile regression decompositions, we decomposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…MMSE is a commonly used clinical screening tool for dementia, but it may lack sensitivity to milder cognitive deficits due to ceiling effects, particularly in individuals with higher education levels [36]. Therefore, the lack of association between education and MMSE at higher levels of MMSE may be a result of such ceiling effects, which were also noted by Ford and Leist [11]. Additionally, as discussed above, the sample in our study was relatively young (aged 58–68), and in these ages, few persons have experienced cognitive decline to the point of scoring in the lower half of the MMSE scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMSE is a commonly used clinical screening tool for dementia, but it may lack sensitivity to milder cognitive deficits due to ceiling effects, particularly in individuals with higher education levels [36]. Therefore, the lack of association between education and MMSE at higher levels of MMSE may be a result of such ceiling effects, which were also noted by Ford and Leist [11]. Additionally, as discussed above, the sample in our study was relatively young (aged 58–68), and in these ages, few persons have experienced cognitive decline to the point of scoring in the lower half of the MMSE scale.…”
Section: Discussionmentioning
confidence: 99%
“…While the average effect of an exposure on an outcome can be a useful metric, it provides limited information of how the effect of an exposure might differ across various levels of the outcome. Recent studies have indicated that educational differences in cognitive performance among younger people [ 10 ] and adults [ 11 ] may vary at different levels of performance distribution, with larger differences found at low levels of performance. If these findings translate to older adults, the seemingly protective effect of education on cognitive aging could be weak or even nonexistent for persons with higher cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational performance in school is associated with learning new tasks, recalling what is important and useful, and solving problems. Occupational performance involves leaning how to acquire efficient work habits, strategies and expertise to apply throughout one’s career ( Ford and Leist, 2021 ).…”
Section: Introductionmentioning
confidence: 99%